Improving employee job satisfaction in aviation industry - Samto Hadi Isnanto (Institut Teknologi Dirgantara Adisutjipto, 2021)
Job satisfaction is an important issue in an organization. Job satisfaction has been talked about over and over again because of the importance it has in both individual and group behaviour, which will affect in the productivity of an organization. Even though the role of job satisfaction is important in an organization, it is sometimes unnoticed and ignored by the management which in turn results in a decrease of organizational work performance. This study aims to answer why job satisfaction is important and how to improve it in aviation industry. The method used in this research is a literature review by finding specific researches that corresponds to the topic discussed, which is job satisfaction, to integrate them into a concise conclusion. This research uses samples from published journals in the last 10 years (2011 – 2021) found through google scholar with the main variable job satisfaction. The result of this study shows that based on the literature reviews of different journals, job satisfaction proves to strengthen employee engagement and organizational commitment, decreases the rate of employee turnover and improves employee productivity. There are a few proven ways to increase job satisfaction in aviation industry which is creating a conducive/positive work environment, applying reward and recognition management, developing the potential skills of employees and continuous evaluation and measurement of employee job satisfaction.